Biomechanical Regulatory Factors and Therapeutic Targets in Keloid Fibrosis - Feng, Fan; Liu, Mingying; Pan, Lianhong; Wu, Jiaqin; Wang, Chunli; Yang, Li; Liu, Wanqian; Xu, Wei; Lei, Mingxing (Frontiers in Pharmacology, 2022)
Keloid is a fibroproliferative skin disorder caused by abnormal healing of injured or irritated skin and characterized by excessive extracellular matrix (ECM) synthesis and deposition, including excessive of collagen disorders and calcinosis, which improve the remodeling and stiffness of Keloid matrix. The pathogenesis of Keloid is very complex, which may include changes in cell function, genetics, inflammation and other factors. In this review, we aim to discuss the role of biomechanical factors in the formation of Keloid. Mechanical stimulation can lead to excessive proliferation of wound fibroblasts, deposition of ECM, secretion of more pro-fibrosis factors, and continuous increase of matrix stiffness of Keloid. Matrix mechanics resulting from elevated matrix stiffness further activates the fibrotic phenotype of Keloid fibroblasts, thus forming a loop that continuously invades surrounding normal tissue. In this process, mechanical force is one of the initial factors of Keloid, and matrix mechanics leads to the further development of Keloid. Next, the mechanotransduction pathways involved in the formation of Keloid were summarized, such as TGF-β/Smad signaling pathway, integrin signaling pathway, YAP/TAZ signaling pathway and calcium ion pathway. Finally, some potential biomechanics-based therapeutic concepts and strategies are described in detail. Taken together, these findings underscore the importance of biomechanical factors in the formation and progression of Keloid and highlight their regulatory value, and may help facilitate the development of pharmacological interventions that can ultimately prevent and reduce Keloid formation and progression.